Geochemical factors associated with deposition of lower Aptian organic-rich sediments during OAE1a in the Basque-Cantabrian Basin, northern Spain - Herdocia, Carlos; Maurrasse, Florentin J-M. R. (Frontiers in Geochemistry, 2023)
The Early Aptian Oceanic Anoxic Event 1a (OAE1a) is characterized by organic matter (OM) bearing rocks identified worldwide, which also occur in the hemipelagic succession of the Cuchía section, North Basque-Cantabrian Basin (NBCB) in Northern Spain. Previous works identified OAE1a using δ13C calibrated with biostratigraphy of planktonic foraminifera, calcareous nannoplankton, and ammonites. However, the geochemical characteristics that controlled OM sources and the redox conditions during OAE1a are yet to be determined. Therefore, here we present the results of a high-resolution complementary study along 67 m of the succession at Playa de los Caballos beach that highlights how local factors in the basin modulated the effects of increased precipitation during enhanced global hydrological cycles. Samples were analyzed for total inorganic carbon (TIC), total organic carbon (TOC), δ13C, major elements (Al, Ti, Si), redox sensitive trace elements (RSTEs), clay mineralogy, bulk mineralogy, and biomarkers. Carbon isotope segments C2 to C6 were recognized to determine the age of the outcrop. Lipid biomarkers indicated that OM is predominantly marine with significant terrestrial contribution. Terrigenous OM was carried to the basin through pulses of fluvial input as attested by the major elements and by high relative proportions of quartz, feldspar, and clay minerals. Increased terrestrial inputs also enhanced primary production and facilitated OM preservation. Periods with hightened RSTE content correspond with increases in the major elements, thus implying their common provenance. High sedimentation rates together with the presence of less labile OM and the interaction with clay minerals most likely played a major role in preserving the OM. This study further highlights how enhanced hydrological cycles significantly influenced the marine conditions that controlled the expression of OAE1a in the NBCB.